183 Effects of Protein Supplementation on the Gut Bacterial Community Composition of Hybrid Striped Bass, Morone Chrysops X M. Saxatilis. (7th May 2021) - Fowler, Emily; St-Pierre, Benoit; Poudel, Prakash; White, Brandon; Brown, Michael
Abstract: Plant-based protein ingredients have become an attractive substitute for traditional animal sources in the aquaculture feed industry. However, inclusion in carnivorous fish diets is limited due to reduced digestibility, presence of anti-nutritional factors, and increased risk of digestive tract inflammation. To gain further insight on the adaptation of the fish digestive tract environment to plant-based protein sources, intestinal bacterial communities from Hybrid Striped Bass, Morone chrysops x M. saxatilis, fed diets supplemented with different protein sources were compared. Data were generated by Illumina MiSeq 2X300 sequencing of PCR generated amplicons targeting the V1–V3 regions of the 16S rRNA gene. A comparative analysis using the non-parametric Kruskal-Wallis test identified 17 highly represented species-level Operational Taxonomic Units (OTUs) that differed in abundance across dietary treatments (P < 0.05). Notably, OTU SD_McMs-0001 was at its highest abundance in samples from individuals fed poultry-fishmeal (PFM; 47.61% ± 0.92%) and plant protein-based (PP; 43.13% ± 1.76%) diets, while it was found in much lower abundance in the non-supplemented control diet samples (B; 4.29% ± 0.92%). It was predicted to be a novel species of the family Peptostreptococcaceae based on its limited 16S rRNA gene sequence identity to its closest valid relative (Peptostreptococcus russellii, 91%). In contrast, three Proteobacteria-affiliated OTUs (SD_McMs-0002, SD_McMs-0003, and SD_McMs-0004) were most highly represented in B diet samples, with averages of 30.28%, 27.22%, and 13.54%, respectively. They were in much lower abundance in the PFM and PP samples, with averages ranging between 0.18% and 4.82%, respectively. Based on 16S rRNA sequence comparisons, they were predicted to be strains of Plesiomonas shigelloides (99%), Ralstonia pickettii (99%) and Sphingomonas elodea (99%), respectively. These results indicate that protein supplementation affects gut bacterial community composition of Hybrid Striped Bass, but that the type of protein used has minimal or no detectable impact.